Architecture of the 8 MDa Hdr–Vhu–Fwd super-assembly in class I methanogens - Sophia Paul; Tomas C. Pascoa; Max A. Klamke; Stefan Bohn; Frank Abendroth; Darja Deobald; Olalla Vázquez; Sven T. Stripp; Jan M. Schuller (Nature, 2026)
Abstract Methanogens are central to global carbon cycling and among the largest biological sources of methane, a potent greenhouse gas 1 . At the heart of their energy metabolism lies the Hdr–Vhu–Fwd super-assembly, which couples H 2 oxidation with CO 2 reduction through flavin-based electron bifurcation. Here we present the cryogenic electron microscopy structure of the Hdr–Vhu–Fwd super-assembly from Methanococcus maripaludis , revealing an 8 MDa complex comprising 252 polypeptide chains and over 600 redox cofactors. Cryo-electron tomography further support that this super-assembly forms an intact structure within the cytoplasm of intact cells. This architecture comprises two hexameric HdrABC–Vhu rings linked by a tetrameric FwdF core, forming a continuous, circular electron chain. In this unique arrangement, 12 polyferredoxin subunits (VhuB) connect the Vhu–Hdr and Fwd complexes, thereby coupling electron bifurcation with CO 2 reduction and directly linking the last and the first step of methanogenesis. Moreover, we identify a modular variant of the complex in which the [NiFe]-hydrogenase Vhu is substituted by tungsten-containing formate dehydrogenase (FdhAB), indicating flexible integration of electron-input modules facilitating metabolic adaptation under diverse environmental conditions 2 . Analysis of the taxonomic distribution reveals that this architecture is specific to class I methanogens and is distinct from the smaller Hdr–Fmd complex of class II 3 . Together, our study reveals that the the Hdr–Vhu–Fwd super-assembly has a modular and adaptable bioenergetic assembly, suggesting a lineage-specific architecture to adapt to diverse anaerobic niches.